A common transcriptional activator is located in the coding region of two replication-dependent mouse histone genes. - Hurt, M M (1991)
There is a region in the mouse histone H3 gene protein-encoding sequence required for high expression. The 110-nucleotide coding region activating sequence (CRAS) from codons 58 to 93 of the H3.2 gene restored expression when placed 520 nucleotides 5' of the start of transcription in the correct orientation. Since identical mRNA molecules are produced by transcription of the original deletion gene and the deletion gene with the CRAS at -520, effects of the deletions on mRNA stability or other posttranscriptional events are completely ruled out. Inversion of the CRAS sequence in its proper position in the H3 gene resulted in only a threefold increase in expression, and placing the CRAS sequence 5' of the deleted gene in the wrong orientation had no effect on expression. In-frame deletions in the coding region of an H2a.2 gene led to identification of a 105-nucleotide sequence in the coding region between amino acids 50 and 85 necessary for high expression of the gene. Additionally, insertion of the H3 CRAS into the deleted region of the H2a.2 gene restored expression of the H2a gene. Thus, the CRAS element has an orientation-dependent, position-independent effect. Gel mobility shift competition studies indicate that the same proteins interact with both the H3 and H2a CRAS elements, suggesting that a common factor is involved in expression of histone genes.